INCOG 2.0 Guidelines for Cognitive Rehabilitation Following Traumatic Brain Injury, Part I: Posttraumatic Amnesia. Issue 1 (January 2023) - Ponsford, Jennie; Trevena-Peters, Jessica; Janzen, Shannon; Harnett, Amber; Marshall, Shawn; Patsakos, Eleni; Kua, Ailene; McIntyre, Amanda; Teasell, Robert; Wiseman-Hakes, Catherine; Velikonja, Diana; Bayley, Mark Theodore; et al.
Abstract : Introduction: Posttraumatic amnesia (PTA) is a common occurrence following moderate to severe traumatic brain injury (TBI) and emergence from coma. It is characterized by confusion, disorientation, retrograde and anterograde amnesia, poor attention and frequently, agitation. Clinicians and family need guidelines to support management practices during this phase. Methods: An international team of researchers and clinicians (known as INCOG) met to update the INCOG guidelines for assessment and management of PTA. Previous recommendations and audit criteria were updated on the basis of review of the literature from 2014. Results: Six management recommendations were made: 1 based on level A evidence, 2 on level B, and 3 on level C evidence. Since the first version of INCOG (2014), 3 recommendations were added: the remainder were modified. INCOG 2022 recommends that individuals should be assessed daily for PTA, using a validated tool (Westmead PTA Scale), until PTA resolution. To date, no cognitive or pharmacological treatments are known to reduce PTA duration. Agitation and confusion may be minimized by a variety of environmental adaptations including maintaining a quiet, safe, and consistent environment. The use of neuroleptic medications and benzodiazepines for agitation should be minimized and their impact on agitation and cognition monitored using standardized tools. Physical therapy and standardized activities of daily living training using procedural and errorless learning principles can be effective, but delivery should be tailored to concurrent levels of cognition, agitation, and fatigue. Conclusions: Stronger recommendations regarding assessment of PTA duration and effectiveness of activities of daily living training have been made. Evidence regarding optimal pharmacological and nonpharmacological management of confusion and agitation during PTA remains limited, with further research needed. These guidelines aim to enhance evidence-based care and maximize consistency of PTA management.